Early Childhood Reading Learning Based on Information Technology - Syofriend, Yul (Universitas Negeri Semarang, 2014)
Aspects of early childhood development can be stimulated by providing learning activities that attract multi-media and methods. The research was conducted in kindergarten Earth Limaumanis Padang VI aims to determine the reading level of development as one part of the learning aspects of language development through multi-media computer. Learning to read children stimulated with software compact disc reading programs. The research method uses a class room with two action research cycles, each cycle of the three meetings. The results of this study demonstrate the effectiveness of the development of children with significant reading through the analysis of the data indicated an increase in the attitude of children who read well and good 92,5%. Increase in the child's well read and well 87,5%. This means that in general the development of learning to read the child has reached the minimum completeness criteria (KKM). Therefore, this assessment is stopped until the second cycle at the meeting of 4, because of the thoroughness of learning to read at least in the development of children has been reached.How to citeSyofriend, Y. (2014). Early Childhood Reading Learning Based on Information Technology. Indonesian Journal Of Early Childhood Education Studies, 3(1), 18-30. doi:10.15294/ijeces.v3i1.9471